The handbook of global education policy - Mundy, Karen E. Karen Elizabeth 1962-; Green, Andy 1954-; Lingard, Bob; Verger, Antoni 1975- (Handbook of global policy series)
"This innovative new handbook offers a comprehensive overview of the ways in which domestic education policy is framed and influenced by global institutions and actors. Surveys current debates about the role of education in a global polity, highlights key transnational policy actors, accessibly introduces research methodologies, and outlines global agendas for education reform. Includes contributions from an international cast of established and emerging scholars at the forefront of the field thoughtfully edited and organized by a team of world-renowned global education policy experts. Each section features a thorough introduction designed to facilitate readers’ understanding of the subsequent material and highlight links to interdisciplinary global policy scholarship. Written in an accessible and engaging style that will appeal to domestic and international policy practitioners, social scientists, and education scholars alike"--